If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + -4x = 11 Solving 37 + -4x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + -4x = 11 + -37 Combine like terms: 37 + -37 = 0 0 + -4x = 11 + -37 -4x = 11 + -37 Combine like terms: 11 + -37 = -26 -4x = -26 Divide each side by '-4'. x = 6.5 Simplifying x = 6.5
| x-.15x=24251.76 | | 2(4x+1)=6x+10 | | 3+35x=20x+9 | | a-(-3a)=20 | | X^2=-4kx-1 | | 5y-3x-7+7x+13= | | 10-n=8 | | x+x+x+3=180 | | (x+3)(x+2)=(x+3)(5x+1) | | 3/5x6 | | 3/35x6 | | 55A^2+28A-3= | | 4.9=n+-2.6 | | r^4+2r^3+r^2+8*r-12=0 | | 4x+14=-22-2x | | 21=-4+9(y+8) | | 6x+y=50 | | 7*2=z*2/2 | | 3(-2)-1.2y=-2.4 | | r^4+2r^3+r^2+8r-12=0 | | 2(8-c)=-2 | | 66-2x=10-10x | | 17.5=32t-16tsquared | | 8-m=4 | | 8x-5=180 | | 20-g=13 | | 7x-103=3x-7 | | 3x+2=28-(3x+2) | | 3x-1.2(2)=-2.4 | | 12+f=16 | | 5+12x=-6+x | | t=60+16t-t^2 |